Immune Responses of the Critically Endangered Yangtze Finless Porpoises (Neophocaena asiaeorientalis ssp. asiaeorientalis) to Escalating Anthropogenic Stressors in the Wild and Seminatural Environments - Nabi, Ghulam; Li, Ying; McLaughlin, Richard W.; Mei, Zhigang; Wang, Kexiong; Hao, Yujiang; Zheng, Jinsong; Wang, Ding (Frontiers in Physiology, 2020)
Increasing anthropogenic stressors are potential threats to biodiversity conservation and management of Yangtze finless porpoises (YFPs). The objective of this study was to indirectly compare the habitat quality of a natural reserve, Poyang Lake and a semi-natural reserve, the Tian-E-Zhou Oxbow (TZO) in terms of anthropogenic stressors by investigating different stress and immunological parameters in the blood of YFPs. Samples from a total of 74 YFPs from the TZO (n=43) and Poyang Lake (n=31) were collected and analyzed. The animals were divided into the ontogenetic groups male calf, female calf, juvenile female, juvenile male, adult male, and into the reproductive groups pregnant female, lactating female, and pregnant plus lactating. The blood from all the animals was analyzed for general stress (HSP14, SOD1, TXN and FTL), metabolic stress (ACAT2 and THRA), and immunity-related genes (IL12p40, IFNγ, TNFα; IL1α, IL1ra, COX2, CRPL, IL4 and IL8) using qPCR. YFPs living in Poyang Lake showed an increased relative expression pattern for IFNγ, IL1ra, IL4, ACAT2, and CRPL across all the ontogenetic groups with significantly higher expression in adult males. In contrast, YFPs living in the TZO showed a significantly higher expression in 13 of 15 genes analyzed in the male calf group. Across the reproductive states for porpoises living in Poyang Lake, 8 of 15 genes in the pregnant female and 3 of 15 genes in the pregnant plus lactating group had a significantly higher expression level. However, in YFPs living in the TZO, 8 of 15 genes showed significantly higher expression in the pregnant and lactating group. There was significantly higher expression of most of the genes in porpoises living in the TZO compared to age-matched groups from porpoises living in Poyang Lake. The exception was the pregnant female group. The higher relative expression of stress and immune genes in the TZO porpoise population compared to porpoises living in Poyang Lake suggests the effects of worsening habitat quality, possibly indicating water pollution and lack of feeding resources.